A digital approach for one-step formation of the supra-implant emergence profile with an individualized CAD/CAM healing abutment. Issue 3 (July 2016) - Joda, Tim; Ferrari, Marco; Braegger, Urs
Abstract: Purpose: This Technical Procedure describes a novel workflow for a one-step formation of the supra-implant emergence profile in the esthetic zone – the 'Digitally Flip Technique' (DFT). Methods: After implant placement, a post-operative intra-oral optical scan (IOS) was performed to capture the final three-dimensional implant position. Based on the superimposition of the digitally slice-wise DICOM-segmentation of the digitally flipped (mirrored) contra-lateral tooth and the STL-file of the IOS, an individualized healing abutment was CAD/CAM-fabricated out of PMMA-based restoration material in a fully digital workflow and seated at the stage of reopening surgery. One single treatment step was necessary for final modulation of the supra-implant mucosa architecture in order to mimic the morphological emergence profile of the contra-lateral tooth within a short-span time frame of four days after insertion of the individualized healing abutment. Conclusions: The implant crown emergence profile could be shaped immediately after reopening according to the three-dimensional radiographic contour of the digitally flipped contra-lateral tooth. Estimating the emergence profile or time-consuming step-by-step conditioning of the mucosa through an additionally produced implant provisional was therefore avoided.